Pulmonary Adenocarcinoma in a Bitch - Detection by Multimodal Imaging Diagnostic Methods - Silveira Stanquini, Camila; Tagliatela Tinto, Stéfany; Rodrigues Gomes, Diego; de Nogueira Aires, Luiz Paulo; Mazeto Ercolin, Anna Carolina; Macedo Rihs, Pedro Gustavo; de Francisco Strefezzi, Ricardo; Rossi Feliciano, Marcus Antonio (Acta Scientiae Veterinariae, 2025)
Background: Primary pulmonary neoplasia, although considered uncommon in dogs, may have its significance underestimated due to diagnostic challenges. The search for alternatives that provide relevant information for both diagnosis and prognosis is crucial for guiding therapeutic decisions. In this context, the combination of multimodal diagnostic methods and the application of techniques such as elastography and contrast-enhanced ultrasound (CEUS) have shown promising results. These modalities can provide predictive data for malignancy, particularly in patients whose debilitated condition may discourage the use of more invasive diagnostic techniques or those requiring anesthetic preparation. Case: A 12-year-old mixed-breed bitch, weighing 19.5 kg, was attended with a history of respiratory clinical signs persisting for approximately 1 year, with recent worsening. During physical examination, in addition to the primary complaint, the patient presented nodules in the mammary chain, which cytological analysis revealed an active chronic inflammatory process. Due to the main complaint and the characterization of the nodular structures in the mammary chain, thoracic radiography was requested for pulmonary evaluation. Radiographic findings revealed a pulmonary nodule measuring approximately 6.5 cm in diameter in the right middle lung lobe, along with a predominant unstructured broncho-interstitial lung pattern, dilation of the main bronchi, and dorsal displacement of mediastinal structures. To obtain complementary information regarding the pulmonary neoformation, ultrasonographic techniques - including B-mode imaging, elastography, and CEUS - were performed, all of which suggested malignancy. Additionally, computed tomography (CT) was conducted to further detail the radiographic findings and delineate the lesion’s topography and dimensions. The combination of these imaging modalities was fundamental for clinical decision-making and surgical planning. A pulmonary lobectomy was performed to remove the caudal and cranial lobes of the right hemithorax, which were compromised by the tumor and adhesions, along with a tracheobronchial lymphadenectomy (medial and right lymph nodes). Histopathological analysis confirmed malignancy, diagnosing papillary pulmonary adenocarcinoma, with severe bacterial suppurative pneumonia, hemorrhage, and marked focal pulmonary edema in adjacent lung tissue. Additionally, tracheobronchial lymph nodes exhibited hyperplasia associated with reactivity. The patient died 2 weeks after surgery. Discussion: This case report aims to demonstrate the applicability of multimodal imaging diagnostics in the identification of primary pulmonary neoplasms and the benefits of combining contemporary techniques with those traditionally used in clinical practice for the characterization of malignancy-associated factors and therapeutic decision-making. B-mode ultrasound provided information regarding the shape, echogenicity, and echotexture of the neoformation, along with B-lines adjacent to the altered tissue. Elastography revealed increased stiffness of the pulmonary mass, a finding suggestive of malignancy. CEUS provided details about the tumor’s perfusion and contrast enhancement pattern, showing non-homogeneous, centrifugal filling with hypoenhancement in the wash-in, peak, and wash-out phases - features indicative of malignancy. These findings highlight the potential value of these techniques in guiding similar cases and future studies on primary pulmonary neoplasia in dogs, as well as in expanding the routine applicability of CEUS and elastography in veterinary practice. Keywords: pulmonary adenocarcinoma, malignant neoplasm, multimodal imaging, elastography, contrast-enhanced ultrasound, CEUS, dog.